The detection efficiency of digital PCR for the virulence genes of waterborne pathogenic bacteria - Xiaojie Shi (IWA Publishing, 2021)
Waterborne pathogens are the primary concern for the safe reuse of wastewater. Although digital PCR (dPCR) is considered promising for absolutely quantitating genes, the detection efficiency of dPCR is affected by many factors. This study tested eight virulence genes of pathogenic bacteria on a control plasmid and reclaimed water samples with reported primer–probe sets and designed ones on quantitative PCR (qPCR) and dPCR. Probe efficiency, data analysis, and PCR inhibition were found to affect the detection efficiency of dPCR. Firstly, poor probe quality, which is determined by probe quenching and activation efficiencies, was the main cause of PCR failure. Secondly, even if the PCR was successful, the probe quality and signal intensity could still affect the quantitative process. Manual analysis of dPCR data on the weak signal intensity would significantly reduce errors. And lastly, the sensitivity of PCR inhibition was lower in dPCR than qPCR, but inhibition still existed. The dPCR produced various detection efficiencies for different targets in one sample indicating inconstant inhibitory effects. Dilution was still the proper approach to overcome inhibition, but decreased the detection limit. More studies are required to ensure accurate waterborne pathogen quantitation by dPCR. HIGHLIGHTS Successful primers and probes are PCR reagent, protocol, and equipment dependent.; Probe quality is determined by quenching and activation efficiencies.; Peak separation of dPCR is critical and needed manual adjustment sometimes.; dPCR is much more inhibition-tolerant than qPCR.; PCR inhibitory effect is different for different PCR reactions.;